Managing Revenue Volatility in a Small Island Economy : The Case of Kiribati - Purfield, Catriona (IMF Working Papers; Working Paper ;, 2005)
The formulation of fiscal policy in Kiribati faces unusual challenges. Kiribati's revenue base is among the most volatile in the world, and it possesses sizeable financial assets. Drawing on lessons from some other countries who experience high volatility in their revenues, this paper proposes a fiscal policy rule for Kiribati which is nested within a medium-term macroeconomic framework that aims to ensure the sustainable use of Kiribati's financial assets while managing the impact of extreme revenue volatility. It also discusses improvements in the institutional fiscal policy framework that could support such a framework.